2016
DOI: 10.15406/japlr.2016.03.00084
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospective Screening of Ricinodendron Heudelotii Seeds

Abstract: Submit Manuscript | http://medcraveonline.com IntroductionThe plant Ricinodendron heudelotii commonly called Njangsa is an oily seed tree that has long been used as a medicinal plant. Its uses includes: an antidote against poison, because the extract of the bark are said to contain lupeol, to cure various diseases such as cough, malaria, yellow fever, stomach pain, rheumatism. Other characteristics of the plant are its aphrodisiac and antiInflammatory properties. It has also been used for treatment of infertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The increase was observed to be concentration dependent as shown in table 3 and was significant at p≤0.05. The increase in serum FSH and LH levels can be attributed to the presence of phytochemicals such as Tannins, Flavonoids, Oxalate, Phenol, Phytate, Alkaloid and Saponin [5]. Flavonoids are found in a considerable amount in Ricinodendron heudelotii seed extract and functions as Anti-oxidant, Enzyme inhibitors, Immune or Hormones modulators [23] and specific Flavonoids are identified to have a wide range of biological properties that has good effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase was observed to be concentration dependent as shown in table 3 and was significant at p≤0.05. The increase in serum FSH and LH levels can be attributed to the presence of phytochemicals such as Tannins, Flavonoids, Oxalate, Phenol, Phytate, Alkaloid and Saponin [5]. Flavonoids are found in a considerable amount in Ricinodendron heudelotii seed extract and functions as Anti-oxidant, Enzyme inhibitors, Immune or Hormones modulators [23] and specific Flavonoids are identified to have a wide range of biological properties that has good effects.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of some metabolites found in plants [2,3], enables them to carry out their therapeutic function through the additive or synergistic action of several chemical compounds acting at single or multiple target sites associated with a physiological process [4], hence the need to evaluate the plant of study for its assumed therapeutic value for the enhancement of reproductive functions in male wistar albino rats. The plant Ricinodendron heudelotii as revealed from study [5] contains phytochemicals that aids its potency to be used as a medicinal plant. Some of the medicinal properties of Ricinodendron heudelotii include; antimicrobial, antiulcer, antihyperlipidemic, and antioxidant biomarkers enhancer in diabetic oxidative stressed wistar albino rats [6].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the beneficial effect that plants exert through the additive or synergistic action of several chemical compounds acting at single or multiple target sites associated with a physiological process as reported by (Singh, 2011;Odinga et al, 2016) yet with less or no side effects, its affordability and availability (Firdous, 2014). In their research, Odinga et al, 2016 found that the plant seed of Ricinodendron heudelotii contains some phytochemicals such as Tannin, Lunamarine, Ribalidine, Spogenin, Catechin, Rutin, Epicatichin, Kaempferol, Naringenin, amongst others. These phytochemicals exhibit various functions such as anti-inflammatory, anti-oxidant, anti-platelet, anti-allergic (Johnson et al, 2012) and anti-ulcer (Odinga et al, 2018).…”
Section: Introductionmentioning
confidence: 99%